Flow predisposition in Brazilian rugby athletes - Silva, Gisele Maria (2018)
Flow describes a mental state in which people seem to flow when they demonstrate a productive and motivated effort. This study sought to understand the significance that rugby athletes attribute to the flow state, the perception of the phenomena in the sports practice and the implications on performance. For that, 8 male athletes participated in the study, representing the juvenile and senior teams submitted to a semi-structured interview. The results indicated that flow occurs in situations that present balance between personal skills and challenges in sports activity. Success in the game, positive emotions, support/encouragement, recognition and overcoming were aspects that marked the experience elected as special. Making use of psychological strategies, high levels of concentration, feeling prepared for the game and positive emotions were cited as fundamental in achieving flow in the game. On the other hand, some aspects, besides causing harm, interrupted the flow: negative emotions, not perceiving one's self as prepared for the challenge, concentration problems, intragroup difficulties. Negative emotions and the feeling that one is not prepared for the challenge were aspects mentioned only by juvenile athletes. The athletes´ speech showed that although they could not describe the flow, they had already experienced this psychological state.